2017
DOI: 10.17977/um031v40i22017p147
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Praktik Kerja Lapangan Terhadap Soft Skill Siswa SMK Bidang Keahlian Jasa Boga Di Kota Malang

Abstract: Abstrak: Tujuan penelitian untuk mengetahui: (1) pengaruh PKL terhadap soft skill; dan (2) berapa besar pengaruh PKL terhadap soft skill siswa SMK Bidang Keahlian Jasa Boga di Kota Malang. Populasi penelitian siswa SMK Bidang Keahlian Jasa Boga yang sudah melaksanakan PKL dengan jumlah sampel 127 responden. Teknik pengumpulan data menggunakan kuesioner. Teknik analisis data menggunakan analisis regresi linier sederhana dan analisis faktor. Hasil penelitian menunjukkan bahwa PKL berpengaruh terhadap soft skill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Meanwhile, creativity and innovation skills do not have a significant influence. This is similar to research conducted by Mustika et al (2017) It was found that there was an influence between apprenticeship on student soft skills. Soft skills in this study represent written communication skills, critical thinking skills and interpersonal understanding.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, creativity and innovation skills do not have a significant influence. This is similar to research conducted by Mustika et al (2017) It was found that there was an influence between apprenticeship on student soft skills. Soft skills in this study represent written communication skills, critical thinking skills and interpersonal understanding.…”
Section: Discussionsupporting
confidence: 89%
“…Field Work is a form of systematic and synchronous implementation of the practice between educational programs at schools/campuses and mastery of skills acquired through work directly in the world of work to achieve a certain level of expertise, that field Work activities greatly increase students' professional awareness (Arifin, 2014;Sukanti, 2014). Soft skills can be honed and improved over time with learning experience (Mustika et al, 2017). This research is relevant to previous study stated that where in a limited-scale trial, students use teaching materials actively and find it easy to understand the materials in the teaching materials (Dewi et al, 2019;Nugraheni & Winarni, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All questions from the Capability instrument were developed by 29 questions and used 4 levels of Likert scale with the type of case study statement so that analysis and high order thinking skills are needed. [12], [14], [19] 6…”
Section: Methodsmentioning
confidence: 99%